2012
DOI: 10.12659/msm.882194
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin and integrin are involved in cholesterol gallstone formation

Abstract: SummaryBackgroundThis study aimed to investigate the role of osteopontin and its receptor, integrin αv, in gallstone formation using human tissue specimens and a guinea pig lithogenic model.Material/MethodsThe nucleation role of osteopontin was determined in patients’ and normal gallbladder bile samples in vitro. Normal gallbladder was the control, and gallstone gallbladders were divided into group I (with normal epithelia) and group II (with degenerated epithelia) based on pathology change. Immunostaining, mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Our previous research revealed that OPN can inhibit cholesterol gallstone formation as an anti-nucleation factor in gallbladder bile, and OPN in gallbladder bile is probably from gallbladder tissues 16 17 . In the current study, we found that the expression of hepatic OPN was increased in GS, and OPN deficiency altered biliary homeostasis and protected against gallstone formation in mice.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our previous research revealed that OPN can inhibit cholesterol gallstone formation as an anti-nucleation factor in gallbladder bile, and OPN in gallbladder bile is probably from gallbladder tissues 16 17 . In the current study, we found that the expression of hepatic OPN was increased in GS, and OPN deficiency altered biliary homeostasis and protected against gallstone formation in mice.…”
Section: Discussionmentioning
confidence: 98%
“…Osteopontin (OPN) is a soluble cytokine and a matrix-associated protein expressed in the majority of tissues and body fluids 14 and is able to control tumour progression and metastasis 15 . Our previous studies demonstrated that OPN can inhibit cholesterol gallstone formation as an anti-nucleation factor in gallbladder bile 16 17 . Another study showed that OPN was highly expressed in the epithelium of stone-laden intrahepatic bile ducts, intramural, extramural glands and stones, indicating that OPN is involved in hepatolithiasis 18 .…”
mentioning
confidence: 99%
“…The cholesterol gallstone pathogenesis is considered multifactorial, and though OPN has been found in normal humans’ gallbladder bile and tissue, the role of OPN in forming GSs is still unknown [ 43 ]. In the current study, there is a relatively higher detection of mRNA OPN expression in hepatic tissue in the GIII when compared with the GII, GIV, and GI.…”
Section: Discussionmentioning
confidence: 99%